Does oil production promote economic growth in OPEC countries? - Quaresma, Tânia Noélia Raposo (2015)
The oil-growth nexus is studied in a panel of OPEC countries, for a long time span (1960-2011), controlling for the specific context of oil production. Their membership to the cartel put them under a common guidance, which originates phenomena of cross section dependence/contemporaneous correlation in the panel. Recent panel data estimators and cointegration analyses are both pursued and discussed, namely confronting the heterogeneity of panels and the countries specific effects. The Driscoll-Kraay estimator reveals to be appropriate to handle the panel properties. The full comprehension of the oil-growth nexus requires the decomposition in short and long run effects to be done. The growth hypothesis was found only in the short run. The results support the resource curse and prove that the cartel’s long run growth goal is not being accomplished. Actually, both oil production and prices are constraining economic growth in OPEC countries.